Small Farm Food Safety, Fresh Produce, Part 3: What's Wrong with this Picture? - Brian Lapinski; Amy Simonne; Marilyn E. Swisher (EDIS, 2007)
FCS8844, a 2-page fact sheet by Brian Lapinski, Amy Simonne, and M.E. Swisher, reviews three different video clips depicting problematic food safety practices on a small farm and provides discussion questions. Published by the UF Department of Family, Youth and Community Sciences, October 2007.